Inventori Haqat (Hafazan Al-Quran Mudah dan Cepat) Bagi Murid Peringkat Permulaan (Mubtadi’) - Fatin Husna Zaidi; Noornajihan Ja‘afar; Muhammad Lukman Ibrahim (Penerbit USIM, 2025)
E-Proceedings International Language and Education Innovation Competition 2024 (I-INNOLED 2024) “Navigating The Future of Language And Education In A Transformative Era” 15-16 October 2024 Organized by : Faculty Of Major Language Studies Editors: Lubna Abd. Rahman, Amiliayanti Abd Halim, Maziahtusima Ishak